Inhibition of MPTP-induced α-synuclein oligomerization by fatty acid-binding protein 3 ligand in MPTP-treated mice. (15th May 2019) - Matsuo, Kazuya; Cheng, An; Yabuki, Yasushi; Takahata, Ibuki; Miyachi, Hiroyuki; Fukunaga, Kohji
Abstract: Accumulation and aggregation of α-synuclein (αSyn) triggers dopaminergic (DAergic) neuronal loss in Parkinson's disease (PD). This pathological event is partly facilitated by the presence of long-chain polyunsaturated fatty acids (LC-PUFAs), including arachidonic acid. The intracellular transport and metabolism of LC-PUFAs are mediated by fatty acid-binding proteins (FABPs). We previously reported that heart-type FABP (FABP3) interacts with αSyn, thereby promoting αSyn oligomerization in DAergic neurons in the substantia nigra pars compacta (SNpc) following 1-methyl-1, 2, 3, 6-tetrahydropyridine (MPTP) treatment. This αSyn oligomerization is prevented in Fabp3 gene knock out mice. We document a novel FABP3 ligand, MF1 (4-(2-(1-(2-chlorophenyl)-5-phenyl-1H-pyrazol-3-yl)phenoxy)butanoic acid), that inhibits αSyn accumulation in DA neurons, thereby inhibiting the oligomerization of αSyn, loss of DAergic neurons, and PD-like motor deficits in MPTP-treated mice. Chronic oral administration of MF1 (0.3 or 1.0 mg/kg/day) significantly improved motor impairments and inhibited MPTP-induced accumulation and oligomerization of αSyn in the SNpc, and in turn prevented loss of tyrosine hydroxylase (TH)-positive cells in the SNpc. MF1 administration (0.1, 0.3, or 1.0 mg/kg/day) also restored MPTP-induced cognitive impairments. Although chronic administration of l -DOPA (3, 4-dihydroxl-l -phenylalanine; 25 mg/kg/day, i.p.) also improved motor deficits, it failed to improve the cognitive impairments. In addition, l -DOPA failed to inhibit DAergic neuronal loss and αSyn pathologies in the SNpc. In summary, the novel FABP3 ligand MF1 rescues MPTP-induced behavioural and neuropathological features, suggesting that MF1 may be a disease-modifying drug candidate for synucleinopathies. Highlights: α-synuclein (αSyn) triggers dopaminergic neuronal loss in Parkinson's disease. We report a FABP3 ligand, MF1 that inhibits αSyn accumulation in MPTP-treated mice. MF1 rescues MPTP-induced behavioural and neuropathological features. MF1 may be a disease-modifying drug candidate for synucleinopathies.